Terapi Islamic Self Healing Terhadap Quality of life pada Klien Gagal Ginjal Kronis dengan Terapi Hemodialisa - Cita, Errick Endra; Wulandari, Tri; Istanti, Yuni Permatasai (Universitas Muhammadiyah Yogyakarta, 2016)
Background. The measurement of health that related to Quality of Life is necessary to find out the impact of the illness to the life. Non pharmacology therapy is being used to enhance patients with chronic renal failure Quality of Life. Islamic Self Healing Therapy is non pharmacology therapy that includes counseling aspect, prayer, dzikir and drinking zam-zam water. The purpose of this research is to prove the effectiveness of Islamic Self Healing Therapy in improving Quality of Life. Methodology. This study design is qualitative using Action Research, with 5 participants and purposive sampling. Collecting data in this study with semi- structured interviews, observation and documentation to explore the Quality of Life and the effectiveness of Islamic Self Healing therapy. Manual data analysis is used to find the theme out.Results. Thematic analysis has been obtained. Four themes have been identified in Qualty of Life of patients with chronic renal failure: the disruption of the status of the physical, the psychological status, and the status of social relationships and environment. Impact of Self Healing Islamic therapy to Quality of Life in patients with chronic renal failure have identified three themes, includes the positive impact on the physical, social and psychological status.Conclusion. Based on an analysis of interviews of all participants with chronic renal failure therapy hemodialsia showed that Islamic Self Healing therapy can improve the Quality of Life, especially in the domain of psychology.Key Word: Chronic renal failure, Islamic Self Healing, Quality of Life.